DETERMINAN PENGGUNAAN MESIN COMBINE HARVESTER DAN DAMPAKNYA TERHADAP PENGGUNAAN TENAGA KERJA DAN PENDAPATAN PETANI PADI DI DESA TELANG SARI KABUPATEN BANYUASIN - Asi Karlina Intan Sari; Imron Zahri; Dessy Adriani (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2017)
e purposes of this research were to: analyze factors that influence the decision of tidal rice farmers in using and not using Combine Harvester in the process of the rice harvest in Telang Sari Village Tanjung Lago District, Banyuasin Regency, The research was conducted on January 2017 in Telang Sari Village Tanjung Lago District, Banyuasin Regency. The research method was survey, with the sampling method was Disproportionate Stratified Random Sampling used 30 samples of farmers that using Combine Harvester and 30 samples of farmers that not using Combine Harvester. The result of this research are : (1) the factors that significant affected the farmers in using or not using Combine Harvester were age of farmers, large land and production; while education, the number of family members, income, social condition and ecological were not significant.; (2) there was difference in labor using between farmers that using and not using Combine Harvester and (3) there was no difference income between farmers that using and not using Combine Harvester.